PETROLOGY AND GEOCHEMISTRY OF LAPAZ ICEFIELD 02205: A NEW UNIQUE LOW-TI MARE-BASALT METEORITE - Anand M.; Taylor L.A.; Floss C.; Neal C.R.; Terada K.; Tanikawa S. (My University, 2006)
LaPaz Icefield 02205 (LAP 02205) is a new low-Ti mare-basalt meteorite that was discovered in the LaPaz Ice Field in Antarctica. This is the first crystalline lunar basalt in the US Antarctic collection and the only 5th unbrecciated mare-basalt meteorite to be discovered to date. The rock has a typical basaltic texture with tabular and elongated pyroxene and plagioclase crystals, and minor olivine grains commonly rimmed by pyroxenes. Core- to rim-zoning in terms of Fe and Mg is present in almost all pyroxene grains. Accessory minerals include ilmenite, chromite, ulvöspinel, troilite, and FeNi metal. This rock is highly enriched in late-stage mesostasis. Free silica is also abundant. In terms of texture and mineralogy, LAP 02205 displays features of low-Ti mare basalts, with similarities to some low-Ti Apollo 12 and Apollo 15 basalts. Whole-rock major- and trace-element compositions confirm the highly fractionated nature of this basalt. The whole-rock REE contents of the meteorite are the highest among all known low-Ti mare basalts. The platinum group element (PGE) contents in LAP are also enriched suggesting the possibility of endogenously enriched source regions or the PGEs generally behaved as incompatible elements during crystal fractionation under low fO2 conditions. Trace-element contents of mineral grains in LAP 02205 display wide variations, suggesting extensive non-equilibrium crystallization. The REE concentrations in the earliest-formed minerals provide constraints on the composition of the parental liquid, which is similar to the measured whole-rock composition. Crystallization modeling of the LAP 02205 bulk composition yields a reasonable fit between predicted and observed mineral phases and compositions, except for the high-Mg olivine cores, which are observed in the rock but not predicted by the modeling. An isochron age of 2929 ±150 Ma for phosphate minerals makes this rock one of the youngest lunar basalts known to date. The young age and specific geochemical characteristics of LAP distinguish it from those of most other low-Ti mare basalts. However, the low-Ti mare basalt meteorite, NWA 032, has a similar young age, and the two meteorites also appear to be closely related from some geochemical perspectives and might have originated from similar source regions on the Moon. © 2005 Elsevier Inc. All rights reserved.